LINGUO-COGNITIVE FEATURES OF PUZZLES IN ENGLISH AND UZBEK LANGUAGES - Nishonova Xurriyat Tojiddinovna (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Abstract .For decades, researchers have debated and investigated the relationship between language and cognitive development, especially in infancy and early childhood. Modular perspectives posit that language development is controlled by specialized mechanisms, much like the olfactory system evolved to detect, learn, and process airborne particles. In this perspective, language learning might be quite independent of other cognitive abilities. By contrast, constructivist and biologically based perspectives tend to emphasize the progressive, experience-dependent emergence of complex skills, including language. These theories postulate that domain-general cognitive capacities and processes are recruited to develop language. The frameworks make distinct predictions: Modular theories expect language-specific learning processes and products.